Youth, Employment, and Social Protection in Portugal: a Relational Analysis of Young People in the Multidimensional Space of the Labor Market - Assis, R. V.; Tavares, I.; Carmo, R. M. (16th Conference of the European Sociological Association: Tension, Trust and Transformation, 2024)
Currently, despite Portuguese society benefiting from the most qualified youth workforce ever, a set of vulnerabilities resulting from job precariousness hinders the integration and permanence of young people in the labor market. As a group particularly susceptible to moments of crisis, young people were the most affected by unemployment during the Covid-19 pandemic, representing 70% of workers who lost their jobs between 2019 and 2020 in the country. However, are all young people equally vulnerable to job instability and insecurity? What dimensions structure the social space of the youth labor market in Portugal? To what extent do their perceptions of institutions in the world of work vary depending on their position in this social space? The main objective of this communication is to present a relational analysis of young people in the labor market developed from the examination of responses given by 5076 young people, aged 18-35, surveyed in 2023 in Portugal. Using different methods such as Multiple Correspondence Analysis and Cluster Analysis, the structuring dimensions of the multidimensional space of the youth labor market will be identified, and the privileged associations between diverse indicators highlighting differences and inequalities among young workers in the country will be examined. In addition to being unprecedented in Portugal, this study aims to contribute to the deepening of sociological knowledge about a population particularly affected by changes in the labor market, as observed through current tensions between work and social protection.